Chemical and sensory properties of South Tyrol red wines from disease-resistant and Vitis vinifera cultivars - Gavin Duley; Adriana Teresa Ceci; Edoardo Longo; Aakriti Darnal; Beatriz Martín-García; Emanuele Boselli (npj Science of Food)
Abstract Disease-resistant hybrid grape cultivars (DRHGCs) are hybrids of Vitis vinifera and other Vitis species that provide greater resistance to specific diseases, including downy and powdery mildew. These have many advantages, but often have unusual chemical and sensory properties. This study examined the link between the chemical and sensory properties of DRHGC red wines from South Tyrol, Northern Italy, using ‘modified rate-all-that-apply’ sensory analysis, projective mapping (‘napping’), and analytical chemistry. The V. vinifera wine was more astringent, with more strawberry and jam aromas, than the DRHGC wines; the DRHGC wines had stronger green bell pepper flavours and aromas. The polyphenol and volatile profiles of DRHGCs were also distinctive, as were the profile of macrocyclic (crown) oligomeric proanthocyanidins. Panellists rated the DRHGC wines as high quality, suggesting that V. vinifera wines are not inevitably preferred.